Social-Economics Integration of Dualistic Settlement Environment at Urban Areas in Indonesia (Case Study in Yogyakarta City) - Muhammad Baiquni (Forum Geografi, 2000)
Dualistic pattern of settlement is a new phenomena in some areas of Indonesian cities. Such phenomena may reate increasing tensions which lead to emerging potential onflicts among different groups. In managing such potential conflicts, it is important to study many aspects of dualistic settlements, not only in term of physical spatial pattern but also socio-economic pattern in various strate as well as various location in the urban and it surround. This research is aimed at understanding the characteristic and process of emerging dualistic sttlements in Indonesia, further this research attempt to study the pattern and the forms of socio-economic integration of the community. The research approach is aimed at understanding the characteristic and process of emerging dualistic settlement in Indonesia, futher this research attempt to study the pettern and the form of socio-economic integration of the community.